Can a trained non‐physician provider perform transrectal ultrasound‐guided prostatic biopsies as effectively as an experienced urologist?. (21st June 2012) - Hori, Satoshi; Fuge, Oliver; Trabucchi, Kay; Donaldson, Peter; McLoughlin, John
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? PSA testing has resulted in a large number of patients being referred to urologists for investigation of potential prostate cancer. Despite limited evidence, non‐physician providers now perform a number of routine urological procedures such as transrectal ultrasound‐guided prostatic biopsies (TRUSP) in a bid to help relieve this increasing workload. In the largest series to date, we provide evidence that an adequately trained non‐physician provider is able to perform TRUSP as effectively as an experienced urologist after an initial learning curve. Objective To evaluate differences in cancer detection rates between a trained non‐physician provider (NPP) and an experienced urologist performing transrectal ultrasound‐guided prostatic biopsies (TRUSP) at a single UK institution. Patients and Methods We retrospectively analysed a prospectively accrued database of patients (n = 440) referred for investigation of an abnormal digital rectal examination and/or a raised age‐specific prostate‐specific antigen (PSA) value undergoing first‐time outpatient prostatic biopsies who were sequentially allocated to either an NPP or a physician‐led TRUSP clinic. Differences in overall and risk‐stratified prostate cancer detection rates were evaluated according to TRUSP operator. Continuous variables were analysed using Mann–Whitney U test whereas categorical variables were analysed using Pearson's chi‐squared test. A multivariate binary logistic regression model was fitted for predictors of a positive biopsy. Results In all, 57.3% (126/220) of patients who underwent physician‐led TRUSP were diagnosed with prostate cancer compared with 52.7% (116/220) in the NPP‐led clinic (P = 0.338). Sub‐group analysis revealed a lower cancer detection rate in men presenting with a low PSA level (<9.9 ng/mL) during the first 50 independent TRUSP procedures performed by the NPP (P = 0.014). This initial difference was lost with increasing case volume, suggesting the presence of a learning curve. Multivariate logistic regression analysis revealed age (odds ratio (OR) 1.054, 95% confidence interval (95% CI) 1.025–1.084, P ≤ 0.001), presenting PSA level (OR 1.05, 95% CI 1.02–1.081, P = 0.001), prostatic volume (OR 0.969, 95% CI 0.958–0.981, P ≤ 0.001) and clinical stage (OR 1.538, 95% CI 1.046–2.261, P = 0.029) to be predictors of a positive prostatic biopsy outcome. The choice of TRUSP operator was not predictive of a positive prostatic biopsy (OR 0.729, 95% CI 0.464–1.146, P = 0.171). Conclusion An adequately trained NPP is able to perform TRUSP as effectively as an experienced urologist after an initial learning curve of 50 cases.